2021
DOI: 10.3991/ijim.v15i11.22023
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Animation Video for Student Environmental Education at Elementary Schools

Abstract: <p>This research and development aim at knowing the effectiveness of web-based animation videos application on environmental education of elementary school students in East Jakarta in Indonesia. Web-based animation videos for environmental education produced consisted of climate change, mangrove forest, waste recycling, biodiversity, and ozone depletion animation video pages.  Student environmental education measured was related to satisfying student natural curiosity, enhancing environmental awareness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…The author in [17] examined the effectiveness of web-based animation videos in the environmental education of elementary school pupils. The research [17] developed web-based animation video pages for climate change, waste recycling, mangrove forest, ozone depletion, and biodiversity.…”
Section: B Use Of Digital Technologies To Address Littering Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The author in [17] examined the effectiveness of web-based animation videos in the environmental education of elementary school pupils. The research [17] developed web-based animation video pages for climate change, waste recycling, mangrove forest, ozone depletion, and biodiversity.…”
Section: B Use Of Digital Technologies To Address Littering Issuesmentioning
confidence: 99%
“…The author in [17] examined the effectiveness of web-based animation videos in the environmental education of elementary school pupils. The research [17] developed web-based animation video pages for climate change, waste recycling, mangrove forest, ozone depletion, and biodiversity. The impact of the intervention was measured via pupils' level of natural curiosity, improvement in environmental awareness, and the pupils' level of pro-conservation values.…”
Section: B Use Of Digital Technologies To Address Littering Issuesmentioning
confidence: 99%
“…Secondly, regarding the services offered, in commercial applications, the number of configuration options and functionalities offered is usually very large [24], so that the systems are not very intuitive [25] for the creator of the content, which, in this case, is the teacher. In this same sense, the teacher is limited to what the system offers him [26], so that if it is necessary to make a change in the coding [27], it will generally not be possible. However, in the proposed tool, the code is open, so whoever wishes to can make changes to adapt it to their needs.…”
Section: Discussionmentioning
confidence: 99%
“…The constraint of Melda & Putri's research was that it had not shown the form of animated videos used to support microbiology learning. Research conducted by Safitri et al (2021), demonstrated the use of animated videos in learning. Limitation of Safitri et al's research was that it had not shown animated videos for each theme in the lesson.…”
Section: Introductionmentioning
confidence: 99%